An implantable cardioverter defibrillator in a patient with triple mechanical valves. Issue 9 (23rd July 2018) - Tan, Alex W. X.; Ho, Kah L.; Ching, Chi K.; Chua, Kelvin C. M.
Key Clinical Message: A patient with permanent atrial fibrillation, triple mechanical prosthetic valve replacements, and nonischemic cardiomyopathy presented with symptomatic high‐grade atrioventricular block. A transvenous implantable cardioverter‐defibrillator system was achieved with the defibrillator lead and bipolar pace‐sense lead in separate anterolateral branches of the coronary sinus with successful defibrillation testing. Abstract : A patient with permanent atrial fibrillation, triple mechanical prosthetic valve replacements, and nonischemic cardiomyopathy presented with symptomatic high‐grade atrioventricular block. A transvenous implantable cardioverter‐defibrillator system was achieved with the defibrillator lead and bipolar pace‐sense lead in separate anterolateral branches of the coronary sinus with successful defibrillation testing.